The Disproportionality of Noisy-Exhaust Enforcement: A Juridical Analysis of Traffic Police Practice in West Java, Indonesia - Satyadi Joko Yuwono; Asti Sri Mulyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The enforcement of noisy-exhaust violations by the Traffic Directorate of the West Java Regional Police (Ditlantas Polda Jabar) raises unresolved legal problems, most acutely when officers confiscate or forcibly remove exhaust systems at the roadside without ticketing procedures. This article examines two questions: whether such enforcement conforms to the principle of proportionality in police law, and the extent of compliance with Article 285(1) of the Traffic and Road Transportation Law (UU LLAJ) read together with Articles 38–46 of the Criminal Procedure Code (KUHAP). Using an empirical juridical method that combines statutory and case approaches with field interviews and non-participant observation analysed qualitatively, the study identifies three enforcement patterns. Only formal ticketing cumulatively satisfies the three sub-principles of proportionality suitability, necessity, and balance whereas forced confiscation breaches both necessity and balance and qualifies as an ultra vires act. Procedural compliance is partial: vehicle stops conform to the law, but technical inspection proceeds without standardised measuring instruments, and confiscation occurs without judicial authorisation, by officers who are not investigators, and without formal records. The article argues that the root of the problem is systemic rather than the misconduct of individual officers namely the absence of standardised operating procedures, a deficit in officers’ legal competence, and the misuse of discretion to justify procedural overreach. Its novelty lies in integrating the proportionality test and the procedural-compliance test into a single two-layered framework of legality.